Development and Validation of a Simple and Sensitive Reverse-Phase High Performance Liquid Chromatographic Method for the Determination of Ibuprofen in Pharmaceutical Suspensions - Kenan G. Elias; Yumen Hilal (مجلة بغداد للعلوم)
The aim of this work was to develop and validate a rapid and low cost method for estimation of ibuprofen in pharmaceutical suspensions using Reverse-Phase High Performance Liquid Chromatography. The proposed method was conducted and validated according to International Conference on Harmonization (ICH) requirements. The chromatographic parameters were as follows: column of octyldecylsilyl C18 with dimensions (150 × 4.6) mm, mobile phase composed of acetonitrile with phosphoric acid with a ratio of 50 to 50 each using isocratic mode, flow rate of 1.5 mL/min and injection volume of 5 μL. The detection was carried out using UV detector at 220 nm. The method was validated and showed short retention time for ibuprofen peak at 7.651 min, with linearity in the studied range of 0.4 - 1.6 mg/mL (R2 = 0.9999) and with great accuracy ]percent recovery was (100.48%), percent relative error(-1.511-1.465)%[ and repeatability (RSD% = 0.112 for Retention time). The detection and quantitation limits were determined to be 0.036 and 0.110 mg/mL, respectively. This method was applied successfully to determine the content of ibuprofen in three commercial pharmaceutical products. Looking at the short time of analysis and the low limit detection, we recommend this method for routine assays in the quality control laboratories and as a good method for stability studies of ibuprofen.